Understanding Customer Citizenship Behavior in Beauty Industry, in Malaysia - Yong, Ming Shiuan (2014)
This paper is studying about customer citizenship behavior in beauty industry, in Malaysia. Many research papers about service industry are available, but no specific journal article is mention on beauty industry in Malaysia. Malaysia market in beauty products and service was growth up steadily, more and more local manufactures try to develop local brand. And beauty practitioners especially spa and massage therapy is over depending on foreign skilled worker while local has traditional technique but no one promote it. This study is helping practitioners to understand customer citizenship behavior and apply suitable marketing strategy to earn bigger market share. Six variables are studied which are customer-based corporate reputation (CBR), brand credibility, credibility of service worker, benevolence of service worker, customer perception on reciprocity, and feeling of trust to test customer citizenship behavior. Statistical Package for the Social Science (SPSS) and Smart PLS 2.0 (Partial Least Squares path modelling) are using for data analysis. Estimated results is shown except credibility and benevolence of service workers, it is different with the survey conducted in United Kingdom. Reasons are the cultural difference and education background influence customer behavior toward service worker. Discussion conclusion and recommendations based on the finding are made in this study. Few suggestions for future research are shown to improve significant and specific of the study.